2019
DOI: 10.1016/j.redox.2019.101121
|View full text |Cite|
|
Sign up to set email alerts
|

LRP1 activation attenuates white matter injury by modulating microglial polarization through Shc1/PI3K/Akt pathway after subarachnoid hemorrhage in rats

Abstract: White matter injury (WMI) is associated with motor deficits and cognitive dysfunctions in subarachnoid hemorrhage (SAH) patients. Therapeutic strategy targeting WMI would likely improve the neurological outcomes after SAH. Low-density lipoprotein receptor-related protein-1 (LRP1), a scavenger receptor of apolipoprotein E (apoE), is able to modulate microglia polarization towards anti-inflammatory M2 phenotypes during inflammatory and oxidative insult. In the present study, we investigated the effects of LRP1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 47 publications
2
88
0
Order By: Relevance
“…In an experimental SAH model, Egashira et al (2015) have demonstrated that increased secretion of MMP-9 from astrocytes and oligodendrocyte precursors caused disruption of the blood-brain barrier (BBB) and subsequent WMI following SAH. Pang et al (2019) have summarized the pathogenesis and underlying mechanisms of WMI after SAH in their systematic review. In this review, authors have indicated that WMI mainly results from five pathophysiologic changes, including BBB disruption, physical and mechanical damage, neuroinflammation, ischemia, and oxidative stress, underlining the importance of targeting WMI in the treatment of SAH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an experimental SAH model, Egashira et al (2015) have demonstrated that increased secretion of MMP-9 from astrocytes and oligodendrocyte precursors caused disruption of the blood-brain barrier (BBB) and subsequent WMI following SAH. Pang et al (2019) have summarized the pathogenesis and underlying mechanisms of WMI after SAH in their systematic review. In this review, authors have indicated that WMI mainly results from five pathophysiologic changes, including BBB disruption, physical and mechanical damage, neuroinflammation, ischemia, and oxidative stress, underlining the importance of targeting WMI in the treatment of SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have mainly focused on studying the injuries of the cortex or hippocampus following SAH; however, white matter injury (WMI) after SAH has not been well addressed. More than half of the central nervous system is composed of white matter, which is more vulnerable to ischemia/hemorrhagic stroke than gray matter (Pang et al, 2019). In our previous study, we found that WMI occurred in the early stage of SAH, which is characterized by amyloid precursor protein (APP) accumulation, myelin basic protein (MBP) degradation, and white matter edema (Peng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…M1 microglia release destructive pro‐inflammatory cytokines, such as TNF‐α, IL‐1β, IL‐6, iNOS, and CD16/32 (Huang et al, ; Pang et al, ), while M2 microglia promote arginase‐1 (Arg1), IL‐10, and CD206 expression (Martinez, Helming, & Gordon, ). We previously demonstrated that suppressing M1 microglial activation ultimately resulted in the attenuation of neuronal and white matter injury as well as brain edema during EBI after SAH (Pang et al, ; Peng et al, ). All these data suggest that biglycan promotes M1 microglial activation.…”
Section: Discussionmentioning
confidence: 98%
“…The modified Garcia and beam balance tests were conducted to evaluate the neurobehavioral function (SAH mice were assessed prior to sham group) at 48 h after SAH by an investigator who was blinded to experimental groups as previously described (Peng et al, ). The modified Garcia test (maximum score = 18) included spontaneous activity (scores 0–3), spontaneous movement of the four limbs (scores 0–3), forelimbs outstretching (scores 0–3), climbing capacity (scores 1–3), trunk touch (scores 1–3), and vibrissae touch (scores 1–3).…”
Section: Methodsmentioning
confidence: 99%